Comparative analysis of tourism indicators for Croatia and selected competitive countries - Maja Buljat (Mednarodno Inovativno Poslovanje)
An increasing number of countries are investing in the development of tourism, thus becoming a key driver of socioeconomic development. The effects of tourism are realized through foreign exchange revenues, job creation, and the development of local and national infrastructure. As an international trade service, inbound tourism has become one of the world's major trade categories.  Tourism in Croatia is considered an important investment driver and a generator of growth in the national economy.  Addressing and development on a competitive basis are determined by the unfavorable macroeconomic environment and business climate in the country. Today's business world is characterized by accelerated development and competitiveness of companies that must stimulate profitable development, measure value creation and continuously learn from success, because only such companies can succeed.  The aim of the paper is to show the economic effects of tourism and show the position of Croatian tourism in relation to competitive countries, in order to confirm the hypothesis that Croatia is a strong competitive country.